Unleashing Creative Performance Accounting Students - Indrawati Yuhertiana (JASF: Journal of Accounting and Strategic Finance, 2023)
In the current VUCA world, creativity and the capacity to think innovatively become valuable advantages and essential tools that help navigate through the turbulent waves of change. This article examines the crucial significance of creativity in improving the academic achievement of accounting students. The study examines how students tap into their creative abilities in the field of accounting education, given the ever-changing nature of the industry and the growing need for novel approaches. This study used an explanatory sequential mixed methods approach to thoroughly examine the elements that impact the creative performance of accounting students. The integration of qualitative and quantitative methodologies offers an in-depth understanding of the diverse factors that contribute to creative abilities in the field of accounting education. There are 213 respondents from sixteen universities in Indonesia involved in the first phase. Further, there are 14 students of the accounting department UPN Veteran Jawa Timur. Three findings have emerged after a comprehensive investigation. There are three categories of students: those who possess creativity in accounting, those who possess creativity in non-accounting subjects, and those who do not possess creativity at all. The article finishes by evaluating the students' inclination to explore novel ideas and methodologies in accounting. The research seeks to illuminate these features to offer insights on cultivating a creative mentality among accounting students, ultimately equipping them for the changing demands of the accounting profession. The findings may have ramifications for creating curriculum and instructional practices that promote and cultivate creative thinking in accounting education.